Novel Centrally Loaded Resonators and Their Applications to Bandpass Filters - Xiu Yin Zhang, Xiu Yin Zhang; Quan Xue, Quan Xue (IEEE transactions on microwave theory and techniques, 2008)
This paper presents several novel centrally loaded resonators and their applications to various types of bandpass filters. Based on the theoretical analysis, it is found that the even- mode resonance of the proposed resonators can be conveniently controlled without affecting the responses at the odd-mode resonant frequencies. Benefiting from this feature, the resonator can be utilized to design not only harmonic-suppressed bandpass filters and dual-band bandpass filters but also tunable bandpass filters. The tunable filter offers a fixed passband and a tunable one. The center frequency of the upper passband can be electrically tuned, whereas the performance of the lower one is maintained constant. To demonstrate these applications, four filters using the proposed resonators are implemented. The experiments verify the theoretical predictions and simulations.